ANALISIS PEMILIHAN SUMBER MODAL PEDAGANG DI PASAR SIMPANG BARU PEKANBARU - Sandres Siahaan; Anthony Mayes; Any Widayatsari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
This research aims to find out the source of merchants capital in Simpang Baru Market Pekanbaru, the factors that influence the selection of the merchants capital source, and whether the Bank Financial Institution has done its job and function properly to channel credit to small business actors.The type of data used is primary data obtained by distributing questionnaires and having interviews to the merchants and data analysis method used is descriptive method, data obtained from the questionnaire is processed by percentage form and put in a table that has been provided.The result of the research showed that the majority of the merchants prefer to use their own sources of capital due to the stigma attached to high bank lending rates and a long bureaucratic path.Keywords : Trader, source capital, Bank lending